What Are Patient Preferences for Integrated Behavioral Health in Primary Care?. (October 2021) - Dunn, Julia Alexandra; Chokron Garneau, Hélène; Filipowicz, Heather; Mahoney, Megan; Seay-Morrison, Timothy; Dent, Kaitlin; McGovern, Mark
Background: Behavioral health services, integrated into primary care practices, have become increasingly implemented. Although patient satisfaction has been studied, limited information exists about patient preferences for integrated behavioral health in primary care and how perceptions may vary.Objective: To determine patient preferences for integrated behavioral health within primary care and explore differences across patient groups.Methods: A self-report survey was distributed within a quality improvement initiative in an academic health system. A brief 8-item self-report questionnaire of perceptions and preferences for integrated behavioral health was administered to 752 primary care patients presenting before their visits at two primary care clinics. Participation was voluntary, responses were anonymous, and all patients presenting during a three-week timeframe were eligible.Results: In general, patients preferred to have behavioral health concerns addressed within primary care (n = 301; 41%) rather than referral to a specialist (7.5%; n = 55). There was no evidence of variation in preferences by demographic characteristics. Comfort levels to receive behavioral health services ( P < .001) and perceived needs being met were significantly associated with preferences for receiving IBHPC ( P < .001).Conclusion: This project provided valuable data to support the implementation of integrated behavioral health services in primary care clinics. In general, patients prefer to have behavioral health issues addressed within their primary care experience rather than being referred to specialty mental health care. This study adds to an expanding pool of studies exploring patient preferences for integrated behavioral health in primary care.